IFN-? as a time-sensitive biomarker during Oropouche virus infection in early and late seroconverters - Oliveira, Euz?bio de (Nature Research, 2019)
In the present study, patients with acute OROV fever were classified as early seroconverters (IgM/IgG positive at baseline) or late seroconverters (IgM/IgG negative at baseline) and the timeline kinetics of the production of chemokines and cytokines were assessed at 1-3, 4-7, 8-10 and ?11 days after patients have reported the first symptoms. Regardless immunoglobulin profile, all OROV fever patients presented higher levels of CXCL8, and IFN-? and lower levels of TNF and IL-10 at baseline as compared to healthy donors (HD). Lower levels of CCL2, CXCL10, and IFN-? and higher levels of CCL2, CXCL10, IL-6, and IL-17A were detected in early and late seroconverters, respectively, as compared to HD. While early seroconverters presented the increasing levels of CCL2 along the timeline, late seroconverters displayed decreasing levels of CCL2, CXCL10, and IL-6 following days of disease onset. Noteworthy was that IFN-? was revealed as universal biomarker of human OROV fever, while CXCL8 & IL-5 and CXCL10 & IL-17 were consistently observed in early and late seroconverters, respectively. Thus, our results suggest that the production of IFN-?, CXCL10, and IL-17 precede the seroconversion bringing novel insights on the immunological events triggered by the OROV disease.